Assessment of interpersonal anxiety in stutters - Ilic Savic, Ivana; Petrović-Lazić, Mirjana (Psihološka istraživanja, 2021)
Stuttering is defined as a speech disorder characterized by involuntary repetitions and prolongations of speech elements, i.e. voices, syllables or words. The evaluation of interpersonal anxiety in stuttering pathology should indicate and encourage a new perspective, to provide a conceptual approach that has the potential to better understand the affective field of a stuttering person by completing a guide to stuttering rehabilitation. The aim of this study was to compare the degree of interpersonal anxiety of stuttering subjects in both typical populations and the potential effect of age differences and different forms of stuttering on the degree of interpersonal anxiety. The sample included 48 subjects, 24 stuttering subjects and 24 non-stuttering subjects. The assessment of interpersonal anxiety was performed using the WILLOUGHBY questionnaire to assess the degree of interpersonal anxiety. The obtained results show that the subjects who stutter are more anxious than the subjects of the typical population [F(1, 44) = 13.66, p < .01]. Stuttering subjects, older age groups showed a higher degree of interpersonal anxiety compared to younger subjects [F(1, 22) = 8.544, p <.01]. There are differences in the degree of interpersonal anxiety in people who stutter in relation to the form of stuttering [F(2, 21) = 80.83, p < .01], people who have a severe form of stuttering are more anxious than people who have a mild and moderate form of stuttering. These disorders are essential for strengthening and supplementing existing prevention measures, but also encouraging the development of new prevention programs to prevent the occurrence of anxiety by gaining the ability to successfully overcome emotional discomfort associated with speech. These findings underscore the importance of stuttering assessment and therapy in adults and suggest that the integration of interventions by speech therapists and clinical psychologists could be beneficial for this population.